Ontogeny and phylogeny: molecular signatures of selection, constraint, and temporal pleiotropy in the development of Drosophila - Artieri, C; Haerty, W; Singh, R (BioMed Central, 2009)
Background: Karl Ernst Von Baer noted that species tend to show greater morphological divergence in later stages of development when compared to earlier stages. Darwin originally interpreted these observations via a selectionist framework, suggesting that divergence should be greatest during ontogenic stages in which organisms experienced varying 'conditions of existence' and opportunity for differential selection. Modern hypotheses have focused on the notion that genes and structures involved in early development will be under stronger purifying selection due to the deleterious pleiotropic effects of mutations propagating over the course of ontogeny, also known as the developmental constraint hypothesis. Results: Using developmental stage-specific expressed sequence tag (EST) libraries, we tested the 2 hypotheses by comparing the rates of evolution of 7,180 genes obtained from 6 species of the Drosophila melanogaster group with respect to ontogeny, and sex and reproduction-related functions in gonadal tissues. Supporting morphological observations, we found evidence of a pattern of increasing mean evolutionary rate in genes that are expressed in subsequent stages of development. Furthermore, supporting expectations that early expressed genes are constrained in divergence, we found that embryo stage genes are involved in a higher mean number of interactions as compared to later stages. We noted that the accelerated divergence of genes in the adult stage is explained by those expressed specifically in the male gonads, whose divergence is driven by positive selection. In addition, accelerated gonadal gene divergence occurs only in the adult stage, suggesting that the effects of selection are observed primarily at the stages during which they are expected occur. Finally, we also found a significant correlation between temporal specificity of gene expression and evolutionary rate, supporting expectations that genes with ubiquitous expression are under stronger constraint. Conclusion: Taken together, these results support both the developmental constraint hypothesis limiting the divergence of early expressed developmentally important genes, leading to a gradient of divergence rates over ontogeny (embryonic < larval/pupal < adult), as well as Darwin's 'selection opportunity' hypothesis leading to increased divergence in adults, particularly in the case of reproductive tissues. We suggest that a constraint early/opportunity late model best explains divergence over ontogeny.